2021
DOI: 10.3389/fpsyg.2021.764209
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, and Convergent and Discriminant Validity of Gaming Disorder Scales: A Meta-Analysis

Abstract: Background: An association between gaming disorder (GD) and the symptoms of common mental disorders is unraveled yet. In this preregistered study, we quantitatively synthesized reliability, convergent and discriminant validity of GD scales to examine association between GD and other constructs.Methods: Five representative GD instruments (GAS-7, AICA, IGDT-10, Lemmens IGD-9, and IGDS9-SF) were chosen based on recommendations by the previous systematic review study to conduct correlation meta-analyses and reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 95 publications
(121 reference statements)
0
20
0
Order By: Relevance
“…Finally, in comparison with another meta-analysis analyzing the reliability of various instruments [ 31 ], the two polytomous versions of the IGDS (IGDS27P and IGDS9P) show higher reliability scores than those found on other similar instruments. This highlights that these versions may be more suitable for the assessment of the IGD.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Finally, in comparison with another meta-analysis analyzing the reliability of various instruments [ 31 ], the two polytomous versions of the IGDS (IGDS27P and IGDS9P) show higher reliability scores than those found on other similar instruments. This highlights that these versions may be more suitable for the assessment of the IGD.…”
Section: Discussionmentioning
confidence: 90%
“…In our study, the four original versions [ 9 ] are analyzed, including the 9-item and 27-item versions with polytomous and dichotomous response. The election of this instrument by Yoon et al [ 31 ] is based on the results of the systematic review by King et al [ 103 ], in which only the 9-item dichotomous and 27-item dichotomous and polytomous versions [ 103 ] were included (p. 4, Table 1 ). Therefore, not considering the four versions could mean an error in the search, since our sample (made in 2021 and updated in June 2022, consulting Scopus, WoS, PsycInfo, and Dialnet databases) already contains articles that use the not-included version (when the review was conducted in these and other databases by King et al [ 103 ]).…”
Section: Table A1mentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis that studied the reliability and validity of 5 Gaming Disorder Scales (GAS-7, AICA, IGDT-10, Lemmens IGD-9, and IGDS9-SF) showed that they had good internal consistency and test-retest reliability. However, few studies had checked for test-retest reliability ( 9 ). A China-based study evaluated the reliability and internal consistency of the “Chinese Internet Gaming Disorder Checklist (C-IGDC)” in determining the presence of Internet gaming disorder ( Chen et al ).…”
Section: The Use Of Accurate Diagnostic Toolsmentioning
confidence: 99%